Measurement properties and feasibility of repeated sprint ability test: A systematic review - Lopes-Silva, J. P.; Ferreira da Silva Santos, J.; Abbiss, C. R.; Franchini, E. (Strength and Conditioning Journal, 2019)
The purpose of this systematic review is to examine the research methodological quality, measurement properties, and feasibility of repeated sprint ability tests. Results showed that testretest absolute and relative reliability was very large to nearly perfect for total work and best sprint performance. However, the fatigue index presented a weak absolute and relative reliability. Total sprint time was able to discriminate performance between player positions, competitive levels, and season phases, whereas the best sprint performance distinguished the competitive levels and playing positions. Total sprint and best sprint time were correlated with the sum of peak speed and neuromuscular measures.